Pelatihan Swamedikasi Dalam Rumah Tangga Di Kelurahan Tarantang - rika - sepriani (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
Health is a healthy state, both physically, mentally, spiritually and socially that allows everyone to live productively socially and economically. Health development as one of the national developments designed for the achievement of awareness, willingness and ability to live healthy for every population to realize an optimal degree of public health. Self-medication is an attempt by someone to overcome a problem of illness or disease without prior agreement with a doctor or health worker. More than 60% of members of the public swarmed the legal basis Permenkes No.919 / MENKES / PER / X / 1993. Swamedication was more focused on handling quickly and effectively without prior intervention by medical consultants, pharmacists, to reduce the workload on the limited resources and labor. The target audience for this community service activity is 30 health cadres obtained through collaboration with the state visited by the health cadres to provide information and understanding to other community members in their neighborhoods. From this dedication activity obtained 1) Increased knowledge and understanding of health cadres about self-medication 2) Increased knowledge and understanding of health cadres about managing drugs in the household.